POSSIBILITIES OF USING MEDICINES AND BIOLOGICALLY ACTIVE SUBSTANCES AS CORRECTIVES FOR THE FORMATION OF PULMONARY FIBROSIS DURING SARS-COV-2 INFECTION AND IN THE POST-COVID PERIOD - Shulgau, Z.T.; Kamyshanskiy , Y.K.; Gulyayev, A.Y. (Eurasian Journal of Applied Biotechnology, 2023)
A systematic review of the literature on the pathophysiology of fibrosis in interstitial lung diseases was carried out. The results of clinical studies of the effectiveness of antifibrotic drugs are summarized. Particular attention is paid to the development of fibrosis associated with Covid-19 infection. The results of the study of the most promising drugs that prevent the development of fibrosis in this pathology are described. The prospect of developing drug therapy based on plant polyphenols is emphasized.